Stakeholder management in the implementation of new performance indicators - Garcia, Kethyllen Cavalcanti; Fortunato, Murilo Henrique Tank (Brazilian Journal of Production Engineering, 2025)
Project management is a key element for achieving effective results, considering the impact of stakeholders. This study aimed to understand the impacts on stakeholders involved in changes to performance indicators in a business association, based on their levels of influence and engagement. For the research, a structured and anonymous consent form questionnaire was applied to capture stakeholders’ perceptions. The methodology involved both quantitative and qualitative approaches, engaging 20 stakeholders. The analysis revealed the importance of managing stakeholders to ensure project success, highlighting that communication and engagement are crucial for the acceptance of changes. A detailed analysis of the responses identified patterns, areas of focus, and greater challenges, allowing the identification of gaps in communication and employee training. It is concluded that successful stakeholder management and changes in indicators can provide a significant competitive advantage, ensure employee engagement and enable performance improvement through these changes. Thus, the study concluded that proper stakeholder management and effective communication are essential for organizational success.